Evaluation of the functional outcome of surgically corrected uretero-pelvic junction obstruction - Regmi, Prabodh; Basnet, Robin Bahadur; Shrestha, Anil; Shrestha, Parash Mani (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Ureteropelvic junction obstruction (UPJO) is a common renal disease where flow of urine is obstructed from renal pelvis to ureter leading to renal function deterioration. This study analysed the functional outcome of patients after Anderson-Hynes (A-H) pyeloplasty for UPJO. Methods: Retrospective analysis was done for renal function outcome on patients who underwent either open or laparoscopic dismembered A-H pyeloplasty during 20 months period from May 2017 to November 2018 in the Department of Urology in Bir Hospital, National Academy of Medical Sciences (NAMS), Kathmandu, Nepal. Renal functional outcome was based on pre and post-operative glomerular filtration rate and split renal function. Ethical approval was obtained from institutional review board (IRB-NAMS). Descriptive analysis of data was performed. Results: Total 22 patients, 15 male and 7 females underwent dismembered pyeloplasty. The age ranged from 18 months to 65 years. Improvement of split renal functions was noted in 18 out of 22 (81.3%). Conclusions: A-H pyeloplasty is effective surgical option for functional renal improvement in patients with obstructive UPJO.